Optical properties of the 3D, 2-2D and 2D transition metal dichalcogenides - Valdivia, G. A. (2015)
In the present work we realize a systematic study of the optical properties of transition metal dichalcogenides using time dependent density functional theory for the determination of excited states of conduction band considering the electron density as a time dependent functional and temporarily affect the screening Coulomb potential which is used in Dyson equation for electric susceptibility determination. We calculate the real and imaginary parts of dielectric function which permit us to observe the absorption coefficient and the plasmon formation for electromagnetic radiation photons from the infrared (25 meV) to ultraviolet (30 eV) range. And we found that the imaginary parts of zz component of the 2D systems have not absorption peaks, meanwhile, the xx, yy and zz components of the 2D systems have not shown plasma frequencies.